Leading with faith and wisdom from the Bible - Stephen J. Perkins; Susan Shortland (Scandinavian Journal for Leadership & Theology, 2024)
This paper explores the integration of biblical wisdom with contemporary leadership theories to inform effective leadership practices. Drawing upon themes and principles from the Bible, the paper proposes a synthesis of biblical insights and modern leadership approaches. It examines the biblical foundations of leadership and presents a model linking biblical themes to relevant leadership theories. The paper suggests that future research should empirically validate these connections through various methods. By investigating the interplay of biblical principles and leadership practices, researchers can build theory informing a more comprehensive understanding of faith-based leadership. Practically, integrating biblical wisdom with contemporary leadership theories can provide valuable insights for leaders seeking to navigate modern organisations while remaining faithful to their spiritual convictions. Research under the proposed rubric may contribute to refining a theologically-grounded and empirically-validated model of leadership that promotes individual, organisational, and societal flourishing.